2018
DOI: 10.26717/bjstr.2018.03.000845
|View full text |Cite
|
Sign up to set email alerts
|

A comparative Study of Serum Lipid Levels in Pre- Eclamptic and Normotensive Pregnant Women in a Tertiary Hospital, Northwest Nigeria

Abstract: a) Background: Pre-eclampsia is one of the most common complications of pregnancy and a significant cause of morbidity and mortality for both the mother and the fetus, especially in developing countries. Despite considerable research, its cause or causes remain unclear.b) Objective: To determine any significant association between pre-eclampsia and lipid profile changes. c) Methodology: A prospective comparative cross-sectional study was carried out among 70 pre-eclamptic and 70 normotensive pregnant women fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…However, the results of the current study vary from other studies 23,53 . This minor difference may be due to the sample types (fasting and random blood samples) and the gestational age of the women.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…However, the results of the current study vary from other studies 23,53 . This minor difference may be due to the sample types (fasting and random blood samples) and the gestational age of the women.…”
Section: Discussioncontrasting
confidence: 98%
“…In this study, the serum concentration of total cholesterol was signi cantly increased among cases than normal controls. This is in line with the studies reported in Ethiopia, India and Nigeria 20,23,49 . Although, the nding of this study was varied from the study conducted in Saudi Arabia 50 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[6][7][8] Pre-eclampsia usually occurs in late second and third trimester affecting biochemical and metabolic processes in our body, hence contributing to fetal complications. [9][10][11][12] various arterial lesions are seen at the implantation site at uteroplacental level in patients of pre-eclampsia. These types of lesions are seen in acute atherosclerosis and they include areas of fibrinoid necrosis and macrophages which are lipid laden are encircling them.…”
Section: Introductionmentioning
confidence: 99%